Performance evaluation of GWO/PID approach in control of ball hoop system with different objective functions and perturbation. Issue 1 (1st January 2018) - Jain, Neeraj; Parmar, Girish; Gupta, Rajeev; Khanam, Iram
Abstract: The present work deals with robustness and comparative analysis of grey wolf optimization (GWO)/proportional-integral-derivative (PID) approach in control of a ball and hoop (BH) system with different objective functions. The BH system is a device consisting of a ball rolling on the rim of a hoop and can be used to analyse the dynamics of liquid slosh problems. The commonly used objective functions are integral absolute error (IAE), integral square error (ISE), integral of square time multiplied by absolute error (ISTAE) and integral of time multiplied absolute error (ITAE). These objective functions have been minimized with the GWO algorithm to obtain parameters of the PID controller for the control of BH system. The robustness analysis of the proposed GWO/PID approach has also been carried out with ±5% perturbation in locations of the poles. The poles of BH system are perturbed by ±5% of the nominal value and the same PID controller tuned by the GWO algorithm has been applied on the perturbed systems. The comparative analysis of GWO/PID approach is demonstrated with several other existing techniques in terms of the transient response's parameters. The results of the GWO/PID approach outperform certain of the existing techniques in the literature, and the performance of the controller hardly alters with perturbation and objective functions; after it is tuned by GWO.